Gestão da sustentabilidade do espaço museológico implantado no patrimônio edificado mediada pela gestão do conhecimento: um estudo a partir do Museu Histórico Casa Padre Toledo em TiradentesMG - Anna Sophia Barbosa Baracho (2018)
The aim of the present study was to deepen and build the binomial "Sustainable Heritage", which represents the correlated synthesis between historical heritage and sustainability, in a historical museum. It intends to subsidize the decisionmaking of the managers of bothbuildings heritage, as well as of museum spaces, with regard to built heritage and sustainability. This possibility emerges from the need to minimize an existing information gap between two areas of knowledge: professionals involved with the area of historical heritage and those with the area of sustainability. Therefore, qualitativequantitativeapproaches were employed when it comes to the use of built heritage reused as museological spaces. In addition, based on the information collected from questionnaires checklist interviews and simple observations, a case study was chosen, within the universeof collected samples, with specific and similar characteristics. The methodologies, using Knowledge Management, led to the survey of the actual situation of a historical building transformed into a museum space. After analyzing the results, a management tool, whichwould be easier and understandable to all those involved with a museological space and with a direct application, was searched. It should also assist and demonstrate the sequential stages of a decisionmaking process for the construction of the Sustainable Heritage. Its applicability allows that before the final decisionmaking process, different conditions and tools can be employed to each dimension of sustainability, for subsequent adaptive reuse,which must occur in a conscious and sustainable way. It can be affirmed that the purpose of "Sustainable Heritage" is still an embryonic stage in Brazil and that the participation and contribution of several areas of knowledge are necessary for its construction and applicationin the built heritage, originally designed for another use.